Maximization of transcription of the serC (pdxF)-aroA multifunctional operon by antagonistic effects of the cyclic AMP (cAMP) receptor protein-cAMP complex and Lrp global regulators of Escherichia coli K-12. - Man, T K (1997)
The arrangement of the Escherichia coli serC (pdxF) and aroA genes into a cotranscribed multifunctional operon allows coregulation of two enzymes required for the biosynthesis of L-serine, pyridoxal 5'-phosphate, chorismate, and the aromatic amino acids and vitamins. RNase T2 protection assays revealed two major transcripts that were initiated from a promoter upstream from serC (pdxF). Between 80 to 90% of serC (pdxF) transcripts were present in single-gene mRNA molecules that likely arose by Rho-independent termination between serC (pdxF) and aroA. serC (pdxF)-aroA cotranscripts terminated at another Rho-independent terminator near the end of aroA. We studied operon regulation by determining differential rates of beta-galactosidase synthesis in a merodiploid strain carrying a single-copy lambda[phi(serC [pdxF]'-lacZYA)] operon fusion. serC (pdxF) transcription was greatest in bacteria growing in minimal salts-glucose medium (MMGlu) and was reduced in minimal salts-glycerol medium, enriched MMGlu, and LB medium. serC (pdxF) transcription was increased in cya or crp mutants compared to their cya+ crp+ parent in MMGlu or LB medium. In contrast, serC (pdxF) transcription decreased in an lrp mutant compared to its lrp+ parent in MMGlu. Conclusions obtained by using the operon fusion were corroborated by quantitative Western immunoblotting of SerC (PdxF), which was present at around 1,800 dimers per cell in bacteria growing in MMGlu. RNase T2 protection assays of serC (pdxF)-terminated and serC (pdxF)-aroA cotranscript amounts supported the conclusion that the operon was regulated at the transcription level under the conditions tested. Results with a series of deletions upstream of the P(serC (pdxF)) promoter revealed that activation by Lrp was likely direct, whereas repression by the cyclic AMP (cAMP) receptor protein-cAMP complex (CRP-cAMP) was likely indirect, possibly via a repressor whose amount or activity was stimulated by CRP-cAMP.